2008
DOI: 10.1007/s00296-008-0564-1
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin mediates PGE2 overexpression through 5-HT2A and 5-HT3 receptor subtypes in serum-free tissue culture of macrophage-like synovial cells

Abstract: Serotonin antagonists show impressive analgesic efficacy in rheumatoid arthritis, osteoarthritis (OA) or fibromyalgia; however, this effect is not well understood. We examined the mechanism of serotonin-induced inflammation and its antagonists in OA. Serotonin receptor subtypes and COX-2 were analysed by RT-PCR from synovial tissue. Serum-free cultures were stimulated with 10 muM serotonin and/or the antagonists ketanserin (5-HT(2A)), tropisetron (5-HT(3)) and parecoxib (COX-2). Prostaglandin E(2) (PGE(2)), tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 28 publications
3
22
0
1
Order By: Relevance
“…Activated macrophages appear to be the major cellular characters capable of elevating angiogenesis by virtue of their secretory products [42]. In the present model, which tries to mimic chronic inflammatory and wound-healing processes, a cascade of inflammatory events is triggered after induction of inflammation by carrageenan and culminates in new blood vessel formation [43,45]. Here, we show that angiogenesis development was progressive and comparable with the inflammatory cell accumulation in rat pouches.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Activated macrophages appear to be the major cellular characters capable of elevating angiogenesis by virtue of their secretory products [42]. In the present model, which tries to mimic chronic inflammatory and wound-healing processes, a cascade of inflammatory events is triggered after induction of inflammation by carrageenan and culminates in new blood vessel formation [43,45]. Here, we show that angiogenesis development was progressive and comparable with the inflammatory cell accumulation in rat pouches.…”
Section: Discussionsupporting
confidence: 50%
“…Nevertheless, little is known about receptor-mediated signals that are involved in the biological activity of TNFα during inflammatory angiogenesis and especially, in the model of air-pouch angiogenesis. More recently Seidel et al suggested that the inflammation might be triggered by stimulation of 5HT 3 receptor subtypes with consecutive overexpression of PGE 2 [42] and it is well known that PGE 2 regulate angiogenesis in inflammatory granulation tissue [43][44][45][46][47]. Also it has been reported that the production of TNFα is inhibited in immune cells by serotonin [30,[48][49][50], and serotonin-stimulated PGE 2 release inhibits TNFα release [51,52].…”
Section: Discussionmentioning
confidence: 98%
“…This was associated with reduced eosinophil recruitment and a concomitant drop in Th2 cytokines, corroborating the idea that 5-HT is a chemoattractant for eosinophils (Boehme et al, 2004). Elevated 5-HT levels were also observed in other Th2 conditions such as murine atopic dermatitis (Soga et al, 2007) or DSS-induced colitis (Ghia et al, 2009b), while in Th1-driven rheumatoid arthritis, 5-HT enhanced the synthesis of prostaglandin E2 (Seidel et al, 2008).…”
Section: -Hydroxytryptaminesupporting
confidence: 74%
“…e l s e v i e r . c o m / l o c a t e / i n t i m p inflammatory pain [11][12][13][14] as well as chemically induced pain [15,16] responded well to 5-HT 3 receptor antagonists, probably because the latter inhibit nociceptor stimulation.…”
Section: Contents Lists Available At Sciverse Sciencedirectmentioning
confidence: 92%